IPTEKS PENCATATAN DAN PERHITUNGAN PAJAK PENGHASILAN (PPh 21) PADA PT.BANK RAKYAT INDONESIA (PERSERO) Tbk. CABANG MANADO UNIT MALALAYANG - Tambingon, Vernando Viki (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Most of the income state normally came from tax and in that case then state should establish its regulations to control the tax. One regulation is income tax article 21 which is tax for individual income. PT. Bank Rakyat Indonesia is one of banks owned by state or government and established for long age. As PT. Bank Rakyat Indonesia have large business then its employees have taxed with income tax article 21. Till recent, the income tax article 21 for employess is applied correctly and follow the rule of income tax regulations.Â